Effect of Thermal Treatment on the 5-Hydroxymethylforfural for Some Types of Honey (Sader and Zater) In the Markets of The Sabratha City - Tariq A. Ahabaal; Elhadi E. Gunbaej; Saeid K. Ogbas; Mawada O. Emdakem; Omaima S. Ebrahem (African Journal of Advanced Pure and Applied Sciences, 2023)
This study was conducted from (6/15/2020) to (1/15/2021) to evaluate the effect of thermal treatment on the content of 5-hydroxymethylfurfural (HMF) for honey (Sader and Zater) in Sabratha, where the total of samples collected was 24 A sample including 12 Sader samples and 12 Zater samples. According to White's method, the two types of honey (Sader and Zater), which totaled 24 samples, were thermally treated through incubation at 40 ° C for 1.5 hours. which is based on UV-Vis Spectroscopy measurement at wave lengths from 284 to 336nm, and the results were compared with Libyan Standard No. 1988. Where a high HMF content was obtained at a high temperature and a longer time when heating all 24 samples by incubating the two types (Sader and Zater) and thus it was concluded that the compound HMF is affected by the action of heat with the passage of time. Where the mean and standard deviation was before thermal treatment for Sader honey (15.64 ± 5.37) and for Zater honey (16.28 ± 5.81), and for after thermal treatment for Sader honey (29.43 ± 14.46) and for Zater honey (24.30 ± 6.90).